Word Formation In Modern Standard Arabic Palestinian And Tunisian - Darsita Suparno; Muhammad Farkhan; Muhbib Abdul Wahab (AIUA Journal of Islamic Education, 2019)
This work discusses about a comparative linguistics on the process of word formation occur in Modern Standard Arabic, Palestinian, and Tunisian. The study was aimed to describe the process of verb and noun formation in three Arabic languages, and to identify sameness and contrariness of articulation of vocabularies and their potential productivity for pedagogical and translation purposes. The study made use of 220 words of all classes taken randomly from Morris Swadesh basic list of concepts as a main guideline to get the data of word formation process. Armed with those basic words, we conducted in depth interview with five post-graduate students of Arabic Letters Department as key informants to get more information on how these three Arabic languages underwent word formation. The data of word formation process, word forms and meaning were then analyzed qualitatively using the theory and concepts of structural linguistics, especially phonology, morphology, and semantics. This study revealed that several words experienced processes of cognates, backformation, phonological variation,prefixes, clipping, derivation, acronym, loanword, blending and metathesis which brought about different spelling, pronunciation, and meanings.